2017
DOI: 10.1097/md.0000000000008270
|View full text |Cite|
|
Sign up to set email alerts
|

Management of and risk factors for regional recurrence in upper lip squamous cell carcinoma

Abstract: Our goal was to evaluate the risk factors for regional recurrence in upper lip squamous cell carcinoma (SCC).A total of 109 patients with upper lip SCC were retrospectively enrolled. Clinical and pathologic information was collected and analyzed.Fifteen (13.8%) patients had a regional metastasis, 2 patients had parotid node metastasis, and no local or distant metastasis was noted. There was neck level I node metastasis in 15 (100%) patients. In multivariate analysis, invasion depth and degree of differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Another study reported no significant difference in the local control and OS rates of patients with and without perineural invasion (23) . In a study involving 109 upper lip-cancer patients, regional recurrence was seen in 13.8% of the sample, while in a multivariate analysis, the invasion depth (p=0.003) and degree of differentiation (p=0.023) were associated with regional recurrence (24) . In another study, involving 144 lip-cancer patients, 84% were stage I-II, and clinical staging was related to a specific higher survival rate (p= 0.0049).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another study reported no significant difference in the local control and OS rates of patients with and without perineural invasion (23) . In a study involving 109 upper lip-cancer patients, regional recurrence was seen in 13.8% of the sample, while in a multivariate analysis, the invasion depth (p=0.003) and degree of differentiation (p=0.023) were associated with regional recurrence (24) . In another study, involving 144 lip-cancer patients, 84% were stage I-II, and clinical staging was related to a specific higher survival rate (p= 0.0049).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have addressed the role of perineural invasion in the development of lymph node metastases (16) . A univariate analysis showed perineural invasion to be significantly associated with lymphatic node recurrence (24) . Another study reported no significant difference in the local control and OS rates of patients with and without perineural invasion (23) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the incidence of squamous cell carcinoma of the lip is high. It constitutes 25% to 30% of all oral cancers which is much more common in the lower lip than the upper lip (16)(17)(18)(19). The role of cumulative ultraviolet radiation in squamous cell carcinoma of the lip is well established (19).…”
Section: Dear Editormentioning
confidence: 99%
“…In the present context, oral squamous cell carcinoma is responsible for more than 90% of oral cancers [2]. The lip squamous cell carcinoma (LSCC) comprises 10% of all cancers of the head and neck region and can be preceded by actinic cheilitis, a potentially malignant disorder [2,3].…”
Section: Introductionmentioning
confidence: 99%